A case report on the novel application of CRRT in renal vein shunting surgery - Guangxu Tang; Hebin Wang; Luyao Liu; Chundong Ji; Junqiu Yi; Lei Zhang; Shiying Liu (Heliyon)
Background: Giant abdominal tumors exceeding 10 cm in diameter are rare and often involve several critical organs and vascular structures. The primary treatment is surgical excision, which presents substantial challenges, including organ preservation, hemorrhage control, and intact tumor removal. Case summary: We present a 46-year-old male with a massive abdominal mass invading the right kidney and inferior vena cava (IVC). To address this, we developed a novel technique using continuous renal replacement therapy (CRRT) renal vein (RV) shunt procedure. A temporary dialysis catheter was placed in the internal jugular vein to divert blood from the left RV to the superior vena cava. After excising the mass and part of the IVC, an artificial blood vessel was used to reconnect the left RV to the IVC. The urine output of the patient was normal during the surgery, and the renal function remained normal during the 343 days' follow-up period. This approach streamlined the surgical procedures, operating time, blood loss, and avoided systemic heparinization through regional citrate anticoagulation. Conclusion: This innovative surgical technique is particularly effective for complex cases requiring simultaneous occlusion of the IVC and both RVs. It enhances patient safety and outcomes and has significant potential for broader application in urology and general surgery. This case highlights the value of surgical innovation in overcoming complex challenges and provides valuable insights for the medical community.